Strategi Branding Elshinta Radio Dalam Membangun Positioning Sebagai Radio Berita - Muhammad Nevo Bizaro; Velda Ardia; Jamiati KN (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Elshinta Radio is a radio station that broadcasts full news broadcasts for 24 hours non-stop and without song interludes, and is the only radio station in Indonesia that has a broadcast concept like this. The research entitled